Referendum debate riposte - Mark Smith (Scottish Journal of Residential Child Care, 2014)
The nub of Garry Coutts' argument in favour of a 'No' vote is that the Independence Referendum is a distraction from 'real' politics. An alternative reading might be that, rather than being a sideshow, the Referendum has provided a focus for a revitalised politics, an outburst of participative democracy. In that sense it is a not an obsession on the part of the political class, as Garry suggests, but a challenge to the caucus politics that has dominated political life for the last couple of decades. For me, and thousands like me, politics has become interesting and relevant again. A couple of weeks ago, I went along to a Referendum event in Muirhouse. Two of the speakers, former senior figures in the Labour and trades union movements were appearing on their first public platform since the Iraq War scunnered them with 'real' politics. The Independence Referendum has reconnected them. Moreover, the fact that voter turnout of around 80% is anticipated might suggest that this debate has caught the imagination of the Scottish people in a way that 'business as usual' politics has singularly failed to do. And the reason it has done so is not that people are obsessed with constitutional niceties but because they begin to imagine what an independent Scotland might be able to do to tackle some of the key issues facing our country. The constitutional issue is not peripheral to tackling issues such as inequality, but central to it.